Endothelin-1 and -3 modulate the neuronal norepinephrine transporter through multiple signalling pathways in the rat posterior hypothalamus - Hope, Sandra Ingrid (2010)
We have previously reported that endothelin-1 and -3 modulate different steps of noradrenergic transmission in the hypothalamus. We showed that endothelins modify neuronal norepinephrine transport activity through the regulation of the kinetic constant and internalization. In the present work we sought to define the endothelin receptors and intracellular mechanisms involved in the downregulation of neuronal norepinephrine uptake induced by endothelin-1 and -3 in the rat posterior hypothalamic region. Results showed that endothelin-1 reduced norepinephrine uptake through ETB receptors, whereas endothelin-3 through a non-conventional or atypical endothelin receptor. In both cases, the effect on norepinephrine uptake was coupled to protein kinase A and C as well as nitric oxide pathways. However, neither protein kinase G nor intracellular or extracellular calcium and calcium/ calmodulin-dependent protein kinase II were involved. In addition, the same intracellular mechanisms participated in the reduction of nisoxetine binding (norepinephrine transporter internalization index) induced by both endothelins. Present findings reveal the underlying mechanisms involved in the regulation of the neuronal norepinephrine transporter by endothelins and further support the role of these peptides in the modulation of noradrenergic transmission at the presynaptic nerve endings in the posterior hypothalamus.